Епістолярій Тараса Шевченка: внесок у його дослідження Михайла Новицького - Карпінчук, Галина; Karpinchuk, Halyna (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті розглянуто внесок шевченкознавця М. М. Новицького (1892–1964) у виявлення та вивчення епістолярію Т. Г. Шевченка. Зокрема, розкрито його заслуги в опрацюванні епістолярію поета з архіву Департаменту поліції та інших архівів Петербурга, Москви, Києва; проаналізовано підготовлені ним наукові праці із цієї теми та окреслено участь у виданнях епістолярію Т. Г. Шевченка./ In this article is relating about the contribution to literature of M. M. Novytskyy (1892–1964). In particular, tells about his work with correspondence of T. H. Shevchenko that was found in archive of Police department and others archives of Peterburg, Moscow and Kyiv. This article shows the part of scientist in the complete edition of letters of T. Shevchenko. Particular attention is paid to determine the pecularities of individual textual decisions of investigador in this editions (dating, selection of the base text, composition in publishing). M. M. Novytskyy was written commentaries and notes, was composing indexes. Him scientific works used to writing of T. H. Shevchenko biography and others works about poet. The scientific works of M. M. Novytskyy was analysed and we ascertain that scientist found about 90 letters of poet and to him, approximately 50 he was printed for the first time and him belong to attribution about 20 letters of T. H. Shevchenko. The work of M. M. Novytskyy with correspondence of T. H. Shev-chenko, which began in 1924 and lasted for the forty years in general has not been appreciated. Edition “Complete works. Vol 3. Letters” (1929) was banned for many years, and the results of scientific work of M. M. Novytskyy used the other philologists in 1950.
The Correspondence of Taras Shevchenko: Contribution to Study it of Mykhaylo Novytskyy
Карпінчук Г. Епістолярій Тараса Шевченка: внесок у його дослідження Михайла Новицького / Галина Карпінчук // Науковий вісник Східноєвропейського національного університету. Сер. «Філологічні науки. Літературознавство». – 2014. – № 9 (286). – С. 39-45.
Keywords: епістолярій; автографи; архів; шевченкознавство; видання епістолярію Т. Г. Шевченка; М. М. Новицький; correspondence; autographs; archive; T. H. Shevchenko studies; editions of correspondence of T. H. Shevchenko; M. M. Novytskyy